LIVING THE REVELATION, AWAKENING HUMANITY: READING SAYYID ALI KHAMENEI AS A VANGUARD OF CONTEMPORARY ISLAMIC CIVILIZATION - Fithri Dzakiyyah Hafizah (Sadra International Institute, 2026)
Sayyid Ali Khamenei is a globally scrutinized figure with a unique public image. He is not only deeply revered but also viewed as a highly controversial leader. His death has sparked a wave of global attention far more massive than ever before. Current global responses tend to polarize into two mainstream currents: Western narratives are oriented toward a negative essentialism that views Sayyid Ali Khamenei’s leadership as rigid and oppressive. On the other hand, the narratives of his supporters tend to be confined within a positive essentialism that views his leadership as flawless, entirely devoid of internal dynamics. This epistemological impasse is the central problem this study seeks to untangle. To achieve this, this paper employs a qualitative content analysis method to dismantle the gap between these simplistic global narratives and the originality of his notions and actions throughout his leadership trajectory. This study attempt to map the dynamics of Khamenei’s thought within the context of post-revolutionary domestic tensions, while simultaneously capturing how Islamic principles and divine revelation are inclusively contextualized into modern realities. Through a decolonial analytical framework, this study argues that Sayyid Ali Khamenei’s thought cannot be reduced to a rigid form of theocracy. Instead, he offers a dynamic contemporary Islamic paradigm for transforming revelation into a system of governance, where Islamic and human values serve as the core foundation for establishing a humanizing social justice; one that both honours human dignity and drives the resurgence of Islamic civilization in the contemporary era.